2018
DOI: 10.1021/acs.joc.8b00541
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid-Controlled Regioselective Phosphorylation of 2-Indolylmethanols with Diarylphosphine Oxides: Synthesis of Highly Substituted Indoles

Abstract: The Lewis acid-promoted phosphorylation of 2-indolylmethanols with diarylphosphine oxides is described. The regioselectivity of the reaction can be modulated by the choice of rare earth metal Lewis acid, offering a highly selective approach to structurally diverse indole derivatives in up to 97% yield for over 50 examples. This strategy features high selectivity, good functional group tolerance, and easy scalability. The utility of this method is further highlighted by facile modification of the products to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 58 publications
1
11
1
Order By: Relevance
“…Soon after, Wang and Kozllowski disclosed the phosphinoylation of 2‐indolylmethanols 59 with diarylphosphine oxides to synthesize C‐3 phosphinoylated indoles 61 under the catalysis of 20 mol% of Yb(OTf) 3 as Lewis acid (Scheme ) . Some mechanistic studies indicated that the strong Lewis acid property of Yb(OTf) 3 played an important role in this C‐3 regioselectivity where it stabilized the cationic intermediate facilitating the formation of the thermodynamic C‐3 phosphinoylated indoles 61 .…”
Section: Direct Phosphorylation Of the Parent Heterocyclescontrasting
confidence: 81%
See 2 more Smart Citations
“…Soon after, Wang and Kozllowski disclosed the phosphinoylation of 2‐indolylmethanols 59 with diarylphosphine oxides to synthesize C‐3 phosphinoylated indoles 61 under the catalysis of 20 mol% of Yb(OTf) 3 as Lewis acid (Scheme ) . Some mechanistic studies indicated that the strong Lewis acid property of Yb(OTf) 3 played an important role in this C‐3 regioselectivity where it stabilized the cationic intermediate facilitating the formation of the thermodynamic C‐3 phosphinoylated indoles 61 .…”
Section: Direct Phosphorylation Of the Parent Heterocyclescontrasting
confidence: 81%
“…Different from Wang and Kozllowski's mechanism, NMR and control experiments suggest that C‐3 phosphinoylated indoles come partially from direct C‐3 phosphinoylation and dominantly from a tandem benzylic phosphinoylation/[1,3]‐P migration/isomerization sequence from 2‐indolylmethanols under our established conditions. In addition, the acidity of the Brønsted acid and the reaction temperature play vital roles in the [1,3]‐P migration of benzylic phosphinoylation products 63 to form C‐3 phosphinoylated indoles 61 or 62 .…”
Section: Direct Phosphorylation Of the Parent Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal‐catalyzed addition of diarylphosphine oxide to 2‐indolylmethanols evidences the same regioselectivity pattern as already observed in similar reactions using carbon nucleophiles. This aspect has been successfully employed using two different metal complexes which are able to drive the addition of diarylphosphine oxides 106 to 2‐indolylmethanols 33 at the selected carbon atom as portrayed in Scheme . The utilization of Yb(OTf) 3 , which is featured by a very stable anion, results in formation of a weak ion pair with the intermediate carbocation allowing a reversible reaction which favors the thermodynamic C‐3 substituted product 107 .…”
Section: Heteronucleophilesmentioning
confidence: 99%
“…Due to the significance of phosphorylated indoles as one of the most important phosphorus‐containing nitrogen heterocycles, the Wang and Kozllowski group recently developed a Lewis‐acid catalyzed regioselective benzylic phosphinoylation of 2‐indolylmethanols with diarylphosphine oxides or ethyl phenylphosphinate . Under the catalysis of Y(Pfb) 3 as rare earth metal Lewis acid, C‐2 phosphinoylmethyl indoles 61 were obtained in up to 97% yields (Scheme ).…”
Section: C(sp3)−p Bond Formationmentioning
confidence: 99%